Pemberdayaan Masyarakat Nelayan Desa Kramat Bungah Gresik melalui Literasi Keuangan dan Pengelolaan Sumber Daya Pesisir Berbasis Ekonomi Biru - Rizqi Fitroh Hamdani; Irma Indira; Aranta Prista Dilasari; Annita Mahmudah (Jurnal Pengabdian Masyarakat, 2025)
This community service activity aimed to improve financial literacy and coastal resource management based on the blue economy approach among fishermen in Kramat Village, Bungah District, Gresik Regency. The main problems identified were the low level of financial literacy and the lack of awareness regarding the importance of sustainable marine resource management. The method applied in this program was Community Based Research (CBR) combined with Participatory Action Research (PAR), which emphasized active community involvement from the planning stage to evaluation. The program was implemented through financial literacy training, mentoring on household and business financial record-keeping, and workshops on processing fish products and fish waste based on blue economy principles. The results showed an increased understanding of simple financial management among fishermen and a 15% growth in household income. In addition, new community business groups and local leaders emerged as drivers of the coastal economy. This activity also encouraged behavioral changes toward more sustainable marine resource management. Overall, the program contributed to strengthening the economic, social, and environmental resilience of coastal communities and supported the achievement of the Sustainable Development Goals (SDG 1 and SDG 14).